O empreendedorismo sustentável na Amazônia - Duarte, Cyro (2011)
This study was designed to analyze future prospects on sustainable entrepreneurship in the Amazon, based on a literature review on the subject. To this end, we analyzed what actions, public and private, could be adopted to encourage such entrepreneurship. Furthermore, a study was made of Agenda 21, the Kyoto Protocol, and examples of sustainable entrepreneurship. Based on these research sources, we can conclude that endogenous interventions will not promote this development, because it is crucial that the private and public sectors become agents of action so that sustainable entrepreneurship is fostered in the Amazon. It is necessary to create conditions to develop the entrepreneurial spirit of the 'people of the forest' so that they can become citizens in the broadest sense of the word. That is, the communities that live in the Forest have jobs and income, and this economic source comes in a sustainable manner originating in the forest, and in this way demonstrating to the communities that the forest is much more valuable alive than dead. The preservation of the Amazon Rainforest, by those who inhabit it, will certainly be guaranteed, since there is no one better to protect it than its own living cores.